A spatial comparison of semi-urban and rural gminas in Poland in terms of their level of socio-economic development using Hellwig's method - Pomianek, Iwona; Chrzanowska, Mariola (Bulletin of Geography. Socio-economic Series, 2016)
The concept of local development remains a crucial one, especially in the context of European Union membership and its support funds. The multidimensional character of local development makes it a subject of interest not only to economists, but also geographers, sociologists and statisticians. The aim of the paper is to present differences in the level of socio-economic development of semi-urban and rural gminas in Poland and to find clusters of gminas with a similar level of development. Hellwig's method was used to compare 2,174 gminas, which showed large development disparities. There is a clear boundary between Eastern Poland with Mazowieckie Voivodship, where the country's capital, Warsaw, is located, and Western Poland. gminas with a high level of development were observed usually on Poland's Baltic coast and suburban areas of Warsaw, Szczecin, Poznań, Wrocław and Kraków. Low level gminas were mostly situated in the peripheries of the eastern voivodships.